2017
DOI: 10.1111/ases.12325
|View full text |Cite
|
Sign up to set email alerts
|

Safe approach to the splenic hilum by first mobilizing the pancreatic tail in laparoscopic splenectomy

Abstract: The current standardized procedure is highly recommended for a safe laparoscopic splenectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Sakamoto et al suggested another approach through mobilising the pancreatic tail first, followed by dissecting the splenic vessels at the hilum before mobilising the spleen. 29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sakamoto et al suggested another approach through mobilising the pancreatic tail first, followed by dissecting the splenic vessels at the hilum before mobilising the spleen. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Recently, He et al 28 introduced a method of splenic hilum manipulation through active exposure of the pancreatic tail. Sakamoto et al suggested another approach through mobilising the pancreatic tail first, followed by dissecting the splenic vessels at the hilum before mobilising the spleen 29…”
Section: Discussionmentioning
confidence: 99%